Gambaran Karakteristik Pasien Gagal Ginjal Kronis Yang Menjalani Hemodialisa Di Rumah Sakit Umum Daerah Dr. Moewardi - Hartini, Sri; , Sulastri, S.Kp., M.Kes (2016)
Kidney disease is a global health problem seen from the increase in incidence, prevalence and morbidity rates. According to the results of a survey conducted by the Association of Nephrology Indonesia (PERNEFRI,) there are approximately 25-30 million people experience a decline in kidney function. In this year, patients with chronic kidney disease (CKD) increased dramatically by 40%. In 2013 RSUD Dr. Moewardi Surakarta has 1733 patients with chronic kidney disease (CKD), in 2014 there are 2526 patients, and in 2015 there are 2550 patients undergoing hemodialysis both inpatient and outpatient. The purpose of this study is to describe the characteristics of patients with chronic kidney disease (CKD) undergoing hemodialysis at Dr. Moewardi General Hospital of Surakarta. This study uses a quantitative method with descriptive approach. The population was patients with chronic kidney disease (CKD) undergoing hemodialysis within 1 week totaling 203 people. This study used a sample of 134 respondents by taking technique accidental sampling. The instrument used was a questionnaire. Data of the research was analyzed by using univariate analysis. The results showed that the highest proportion of chronic kidney disease (CKD) patients aged 51-60 years old were 48 respondents (35.8%), residing in rural areas of 80 respondents (59.7%), male sex 78 respondents (58.2%), low education / basic (primary and secondary school) 64 respondents (47.8%), Civil Servants/PNS 29 respondents (21.6%), married 123 respondents (91.8%), low income (<USD 1.425 million) 58 respondents (43.3%), disease history of hypertension of 56 respondents (41.8%), the habbit of drinking ≥ 8 cups / day 44 respondents (32.9%), the habit of taking drugs / supplements sometimes ( 1-2 times per week) 65 respondents (48.5%). Based on this study, it should be noted about the factors that cause chronic kidney disease was requiring hemodialysis action.